Humans, Animals, Food and Environment: One Health Approach against Global Antimicrobial Resistance - Marcello Iriti; Sara Vitalini; Elena Maria Varoni (MDPI AG, 2020)
Antimicrobial resistance represents one of the most relevant threats to global public health and food security, affecting anyone, of any age, in any country and is responsible for longer hospital stays, higher medical costs and increased mortality. Resistant microorganisms are present in humans, animals, food and the environment, and, therefore, the One Health approach is very promising to counteract antimicrobial resistance, since human health and animal health are connected to each other and with the environment and the latter a potential source of resistant microorganisms. In this context, the need for novel antimicrobial drugs has stimulated the exploration of plant products as a source of novel phytotherapeutics able to reverse antimicrobial resistance when used in combination with conventional antibiotic drugs.